1999
DOI: 10.1046/j.1365-2885.1999.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

The confirmation and control of metabolic caffeine in standardbred horses after administration of theophylline

Abstract: The origin of caffeine detections in equine serum and urine after theophylline administrations was examined. Three different preparations containing theophylline were administered to standardbred mares. Both blood and urine samples were collected. Caffeine was detected and quantified in theophylline administration samples by high performance liquid chromatography (HPLC) and liquid chromatography-tandem mass spectrometry (LC-MS-MS). Further in vitro analysis showed that caffeine metabolites were not detected wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The methylation of theophylline in man and horses has earlier been described by Tang‐Liu and Riegelmann and Todi et al ., respectively. No detectable levels of caffeine were monitored in plasma after oral administration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methylation of theophylline in man and horses has earlier been described by Tang‐Liu and Riegelmann and Todi et al ., respectively. No detectable levels of caffeine were monitored in plasma after oral administration.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, Todi et al . suggested to establish a urinary threshold for caffeine of 1000 ng/mL and a plasma threshold of 250 ng/mL to account for metabolic caffeine after administration of theophylline to racehorses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 150 spectra of different libraries of compounds were studied. The following groups of molecules were investigated: sulfonamides,20–36 benzimidazoles,37–48 carnitines,49–54 amphetamines,55–60 amino acids,61–80 and purines 81–83. It was observed that each of the above groups produced specific fragment ions and neutral mass losses, depending on the functional groups present in the molecules.…”
Section: Resultsmentioning
confidence: 99%
“…LC/MS methods of analysis for salicylic acid, 6) acetaminophen, [6][7][8] theophylline, 9,10) barbiturates, 11) and bromvalerylurea [12][13][14] have been reported, but our examination of the literature has not revealed any method of simultaneous analysis for all of these from biological samples.…”
mentioning
confidence: 83%